Crinoidea from eastern border of the Parnaíba basin (Cabeças Formation, Middle Devonian) - Scheffler, Sandro Marcelo; Silva, Cleber Fernandes da; Fernandes, Antonio Carlos Sequeira; da Fonseca, Vera Maria Medina (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
This manuscript presents a description of crinoids found in the Cabeças Formation (Middle Devonian, Parnaíba basin) collected in km 305 outcrop, in Picos municipality, Piauí state. The material consists in isolated and sparsely arranged columnals in samples of fine-grained sandstone. The specimens are not well preserved, but it was possible to describe three morphotypes (PB/Cb-01, PB/Cb-02 and PB/Cb-03). Two of them (PB/Cb-01 and PB/Cb-02) are represented by a single specimen, and the third morphotype (PB/Cb-03), in great quantity, probably represents the most common crinoid in the ancient sedimentation environment of km 305 outcrop. The form of occurrence of the crinoids (probably parautochthonous) suggests that after their death, they has remained in the sediment-water interface for a long time before their burial. This fact is a further indication that corroborates with the suggested deposition model of the Cabeças Formation in this region, represented by a mouth-bar environment in a flood-dominated fluvio-deltaic system.